Point defect effects on tensile strength of α−zirconium studied by molecular dynamics simulations. (August 2019) - Li, Yingying; Chen, Hong; Chen, Yuting; Wang, Yuhua; Shao, Liang; Xiao, Wei
Highlights: Point defects effects on the tensile strength of α-Zr are studied by Zr are studied by MD simulations. The yield stresses decrease with the increase of the defect concentration. Interstitials decrease the tensile strength the most seriously vs. the vacancies and Frenkel pairs. The formation of interstitial dislocation loops decreases the uni-axial tensile strength. Abstract: Vacancy, interstitial, and Frenkel pair effects on the tensile strength of α − Zr are studied by molecular dynamics simulations. The uni-axial tensile load is along [0001] direction of the α − Zr samples. The yield stresses and the corresponding yield strains decrease with the increase of the defect concentration for the three types of point defects studied. With the same defect concentration, interstitials decrease the tensile strength the most seriously compared with the vacancies and Frenkel pairs. Interstitial clusters form dislocation loops which decrease the uni-axial tensile strength.